2021
DOI: 10.1111/php.13514
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Photobiogoverning Role of Blue Light Irradiation on Viral Replication

Abstract: Most recently, severe acute respiratory syndrome coronavirus-2 has triggered a global pandemic without successful therapeutics. The goal of the present study was to define the antiviral effect and therapeutic action of blue light irradiation in SARS-CoV-2-infected cells. Vero cells were infected with SARS-CoV-2 (NCCP43326) or mock inoculum at 50 pfu/well. After blue light irradiation, the inhibitory effect was assessed by qPCR and plaque reduction assay. When Vero cells were irradiated to blue light ranging fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…ICP34.5 mutant-HSV-1 was shown to have reduced pathogenicity in mice [ 43 ]. Previously, our results revealed continued induction of the autophagic process and prolonged activation of ER stress after the BL irradiation in SARS-CoV-2-infected cells [ 32 ]. As the difference between previous and present data relies on targeting intracellular components and viral species (e.g.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…ICP34.5 mutant-HSV-1 was shown to have reduced pathogenicity in mice [ 43 ]. Previously, our results revealed continued induction of the autophagic process and prolonged activation of ER stress after the BL irradiation in SARS-CoV-2-infected cells [ 32 ]. As the difference between previous and present data relies on targeting intracellular components and viral species (e.g.…”
Section: Discussionmentioning
confidence: 75%
“…Especially, low-level BL exerted anti-proliferative, anti-inflammatory, and anti-metastatic effects, whereas high-level BL induced the apoptosis of cancer cells depending on the number of irradiating photons. More recently, photo-biogoverning properties and the relevant mechanism of the action of BL on the replication of the SARS-CoV-2 virus have been confirmed [ 32 ]. However, the interaction between photo-energy and immune cells engaged in viral infection has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Our results failed to highlight an antiviral effect in already-infected cells as the three papers cited above showed, however the different virus strains treated, and the different devices employed, could account for the results. Indeed, Oh et al [25] observed a partial selectivity in the blue light's action.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that blue light possesses some degree of selectivity. Moreover, Oh et al [25], showing the antiviral effect of blue light on SARS-CoV-2 already-infected cells (450 nm, 5.56 mW/cm 2 , 1.6, 5, 10 J/cm 2 ), reported that an antiviral effect was associated with reactive oxygen species (ROS) production, endoplasmic reticulum stress and autophagy progression, inhibiting apoptosis and promoting cell survival. These studies employed minor irradiance with respect to those employed in the current study (0.1 W/cm 2 ), nevertheless the fluence (3 J/cm 2 ) was comparable [25] or higher [12,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation